(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In didactics, the content essence of the three main types (content-informational, operational-functional and organizational-methodological), which are considered the objective basis for the division of interdisciplinary connections into classes, is covered.The types of inter-system and interdisciplinary Association and their significance as well as their role in the formation of interdisciplinary connections in students and students are discussed.